HEALTH STOCK REACTION TO COVID 19 : INDONESIA CASE - Adrianna Syariefur Rakhmat; Mohammad Hatta Fahamsyah (Jurnal Ekonomi, 2023)
At the beginning of 2020, the world was shocked by the emergence of a new disease which had evolved into the Covid 19 Pandemic for its rapid spread and relatively high death rate. The Covid-19 pandemic created an uncertaitny. This uncertainty can affect negatively on stock, that is, increasing uncertainty will reduce the stock price, volume and return. This research is a quantitative study that measures the response of the health stock sector to the COVID-19 pandemic. The health sector stocks that were sampled were health service providers, especially hospitals. The amount of data observed was 60 days before the announcement of covid and 60 days after the announcement of covid. Meanwhile the analysis technique that will be used is the Paired Sample T Test. The result of this research conclude that the stock price shows a significant difference between before and after the announcement of covid-19 in Indonesia, while the stock returns show insignificant differences, and the stock volume showed mixed results .